A “toolkit” for rural aged care? Global insights from a scoping review - Vaughan, Geraldine; Carson, Dean B.; Preston, Robyn; Mude, William; Holt, Anne-Marie (Frontiers in Political Science, 2022)
Community-based social models of care for seniors promote better outcomes in terms of quality of life, managing chronic illness and life expectancy than institutional care. However, small rural areas in high income countries face an ongoing crisis in coordinating care related to service mix, workforce and access. A scoping review was conducted to examine initiatives that promoted integrated models of multisectoral, collaborative aged care in rural settings which could help respond to this ongoing crisis and improve responses to emergencies such as the COVID-19 pandemic. A systematic database search, screening and a two-stage full text review was followed by a case study critical appraisal. A content analysis of extracted data from included papers was undertaken. Integrated care services, activities and facilities were identified that helped guide the review process and data synthesis. The three included case studies all emphasized key principles that crucially underpinned the models related to collaboration, cooperation and innovation. Challenges to effective care included fiscal and structural constraints, with underlying social determinant impacts. Based on these findings, we describe the genesis of a “toolkit” with components of integrated models of care. Effective care requires aging to be addressed as a complex, interconnected social issue rather than solely a health problem. It demands a series of coordinated system-based responses that consider the complex and heterogeneous contexts (and needs) of communities. Such models are underpinned by leadership and political will, working with a wide breadth of stakeholders across family, community and clinical domains in private and public sectors.